Manajemen Kelompok Kerja Guru (KKG) pada Gugus Flamboyan Kecamatan Pulau Gorom Kabupaten Seram Bagiaan Timur - Darama Rumanama; Th. Laurens; Sumarni Rumfot (LP. Ma'arif Janggan Magetan, 2024)
The aim of this study is to analyze the functions of planning, organizing, implementing, and evaluating the Flamboyan Cluster KKG using qualitative testing methods. The results of the research indicate that the Flamboyan Cluster KKG has successfully established a solid foundation through a clear vision, mission, goals, and strategies in the planning aspect. The structured planning provides direction and measurable goals for the group, creating a collaborative environment for professional growth and the improvement of educational quality. In the organizational aspect, the Flamboyan Cluster KKG demonstrates commitment and a holistic approach in forming an effective teacher working group. Participatory approaches, adjustments to needs, and a focus on developing teacher competencies are key elements for the development of professionalism and teaching quality. In the implementation phase, the application of motivational strategies, focused guidance, effective coordination, and the use of digital communication media create a positive working environment. In-depth understanding of member needs, proactive response to feedback, and commitment to individual professional growth strengthen the group's performance. Regarding evaluation, the Flamboyan Cluster KKG adopts a participatory approach in formulating job standard criteria and suggesting future work program recommendations. Despite logistical challenges, the group successfully involves active members and adapts to environmental changes to enhance the effectiveness of KKG activities and the quality of teacher development in their region.